The role of HbA1c as a diagnostic test for type 2 diabetes mellitus in Bangladesh (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Type 2 diabetes mellitus is a serious chronic disease with microvascular complications such as retinopathy, nephropathy and neuropathy and macrovascular complications such as cardiac, peripheral arterial and cerebrovascular disease. Objective: The aim of the study was to investigate the value of HbAlc as a diagnostic test for type 2 diabetes mellitus in Bangladeshi inclividuals. Methods: This cross sectional study was conducted in the Department of Biochemistry, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. A total 657 patients, who were attended in the one point sample collection centre of Bangabandhu Sheikh Mujib Medical University for oral glucose tolerance test (OGIT) from 1st April 2014 to 30th June 2014, were purposively enrolled in this study. According to WHO criteria and based on OGIT findings study subjects were categorized into Normoglycemic (257), IFG (82), IGT (174), and DM (347). Fasting plasma glucose. HbA1c and plasma glucose at 2 hour after glucose load on OGIT was done from all the study subjects. Results: With a cut-off value of 6.J %, HbAlc had a maximal sensitivity and specificity of 97.0% and 49.0% respectively with a positive predictive value 65.5% and a negative predictive value 94.0%. HbA1c had a sensitivity of 93.0% and a specificity of 63.0% was calculated with a cut-off value of 6.5% with positive predictive value 77.5% and negative predictive value 90.0%. Both fasting plasma glucose levels and 2 hour plasma glucose levels were showed significant positive correlation with HbAlc (r = 0.788, P = 0.000 and r = 0.800, P = 0.000 respectively). Conclusion: The study suggests that measurement of HbAlc could be used to make diagnosis of T2DM in the Bangladeshi population.